The Impact of Financial Incentives and Perceptions of Seriousness on Whistleblowing Intention - Andon, Paul (Journal of business ethics, 2018)
Many jurisdictions have put regulatory strategies in place to provide incentives and safeguards to whistleblowers to encourage whistleblowing on corporate wrongdoings. One such strategy is the provision of a financial incentive to the whistleblower if the complaint leads to a successful regulatory enforcement action against the offending organization. We conducted an experiment using professional accountants as participants to examine whether such an incentive encourages potential whistleblowers to report an observed financial reporting fraud to a relevant external authority. We also examine the effect of perceived seriousness of the wrongdoing on accountants’ intention to whistleblow. We find that a financial incentive results in a higher intention to whistleblow to a relevant external authority. We also find that perceptions of the seriousness of the wrongdoing are significantly and positively associated with accountants’ intention to whistleblow to a relevant external authority. We find a significant interaction between the provision of a financial incentive and the perceived seriousness of the wrongdoing on the intention to report the wrongdoing externally. The intention to report the financial reporting fraud externally is higher when the level of perceived seriousness is higher, regardless of the availability of a financial incentive. However, when the perceived level of seriousness is lower, the presence of financial incentive results in a higher intention to report the financial reporting fraud externally. These findings indicate that the impact of a financial incentive on the intention to whistleblow is moderated by perceptions of the seriousness of the wrongdoing.